Transient Inflammation-Induced Ongoing Pain is Driven by TRPV1 Sensitive Afferents. Issue 1 (10th January 2011) - Okun, Alec; DeFelice, Milena; Eyde, Nathan; Ren, Jiyang; Mercado, Ramon; King, Tamara; Porreca, Frank
Background: Tissue injury elicits both hypersensitivity to evoked stimuli and ongoing, stimulus-independent pain. We previously demonstrated that pain relief elicits reward in nerve-injured rats. This approach was used to evaluate the temporal and mechanistic features of inflammation-induced ongoing pain. Results: Intraplantar Complete Freund's Adjuvant (CFA) produced thermal hyperalgesia and guarding behavior that was reliably observed within 24 hrs and maintained, albeit diminished, 4 days post-administration. Spinal clonidine produced robust conditioned place preference (CPP) in CFA treated rats 1 day, but not 4 days following CFA administration. However, spinal clonidine blocked CFA-induced thermal hyperalgesia at both post-CFA days 1 and 4, indicating different time-courses of ongoing and evoked pain. Peripheral nerve block by lidocaine administration into the popliteal fossa 1 day following intraplantar CFA produced a robust preference for the lidocaine paired chamber, indicating that injury-induced ongoing pain is driven by afferent fibers innervating the site of injury. Pretreatment with resiniferatoxin (RTX), an ultrapotent capsaicin analogue known to produce long-lasting desensitization of TRPV1 positive afferents, fully blocked CFA-induced thermal hypersensitivity and abolished the CPP elicited by administration of popliteal fossa lidocaine 24 hrs post-CFA. In addition, RTX pretreatment blocked guarding behavior observed 1 day following intraplantar CFA. In contrast, administration of the selective TRPV1 receptor antagonist, AMG9810, at a dose that reversed CFA-induced thermal hyperalgesia failed to reduce CFA-induced ongoing pain or guarding behavior. Conclusions: These data demonstrate that inflammation induces both ongoing pain and evoked hypersensitivity that can be differentiated on the basis of time course. Ongoing pain (a) is transient, (b) driven by peripheral input resulting from the injury, (c) dependent on TRPV1 positive fibers and (d) not blocked by TRPV1 receptor antagonism. Mechanisms underlying excitation of these afferent fibers in the early post-injury period will offer insights for development of novel pain relieving strategies in the early post-traumatic period.